PRESERVASI BEKU SPERMATOZOA IKAN CUPANG (Betta splendens) STRAIN HALF-MOON DALAM MADU DAN NACL FISIOLOGIS - Pertiwi, Rika Prihati Cahyaning; Sulistyo, Isdy; Sukardi, Purnama (Jurnal Perikanan Pantura (JPP), 2021)
A study entitled “Chilled Preservation of Spermatozoa Half-moon Strain Fighting Fish ( Betta spendens ) in Honey and Physiological NaCl”, was conducted to determine preserved spermatozoa motility and viability of Fighting Fish in honey and NaCl solutions, under chilling temperature (-25 0 C). The study applied Completely Randomized Design (CRD) to examine three treatments, i.e aquadest, 0.09% NaCl and honey extenders, with quantuplicates. Data, being spermatozoa motility (%) and viability (time in second), were F-tested (ANOVA) and followed by LSD test (P<0.01). After storage of 7 days, the result showed that spermatozoa motility did not differ between treatments, however the viability of spermatozoa were significantly different (P<0.01). The highest viability was observed in sperm stored in extender Honey averaging 368.90±102.16 seconds, compared to the 0.09% NaCl extender (81.79±8.54 seconds), and aquadest (187.90±35.36 seconds). It was concluded that the Honey, NaCl 0.09% and aquadest as extenders could be used as preservation solution fighting fish spermatozoa. The best viability of spermatozoa was observed in honey extender.